Effects of import duty elimination on the EU Fertilizer Market - Bouët, Antoine; Laborde Debucquet, David (International Food Policy Research Institute, 2016)
This report studies the current condition of competition in the European Union’s fertilizer market, and its impact on fertilizers prices. A review of literature shows that prices of fertilizers in Western European countries increased by 123% between 1970 and 2002, while prices in other countries like Brazil decreased by 65%; it also shows that increased concentration is correlated with higher prices or, alternatively, more competition is associated with lower prices. Economic theory suggests that an elimination of European customs and anti-dumping (“import duties”) on fertilizers will lead to a loss for European fertilizer producers, a gain for European farmers, a loss of public revenues, and a decrease of the degree of concentration in the sector. Based on a partial equilibrium model calibrated on recent data characterizing the world and EU fertilizer markets, this report evaluates the potential impact of an elimination of import duties on the conditions of competition in the EU market, including the impact on concentration and fertilizer prices, and an estimation of the overall net welfare effect associated with an elimination of import duties; this includes an assessment of the consumer surplus for EU agricultural producers and a potential for the additional job creation in EU agriculture.